Preliminary Study on Small Long-Life PWR Reactor Design Fueled Thorium with Protactinium as Burnable Poiso - Jubaidah Jubaidah (Universitas Negeri Medan, 2016)
Thorium as fissile material has overweigh advantages compared to Uranium in order to have a long-life PWR reactor without replacement fuel. Additional of Protactinium as a burnable poison is effective to reduce excess reactivity in the beginning of the reactor operation. This study aims to analyze the neutronic, burnup fuel, thermal-hydraulic and kinetic calculations in regard to reactor safety. The calculation is performed with SRAC program using JENDL-32 as data library. The results show that the value of keff for 33 years are still in the range 1.0154 <keff<1.0171 and the burn-up level has increased, due to the additional fissile material as conversion results of Th232 and Pa231. Axial linear power distribution indicates normal distribution pattern. The coolant temperature distribution in the axial direction is quite flat. Key words: PWR, Th-232, U-233, Pa-231, neutronic, thermal-hydraulic, burn-up level, reactor kinetics